HOW EMERGING CONCEPTS AND DIGITAL TECHNOLOGIES CAN RESPOND TO THE CHANGING NEEDS OF THE LEARNERS - Siyaswati Siyaswati (Universitas Lambung Mangkurat, 2018)
Abstract: The goal of this paper is to know how emerging concepts and digital technologies can respond to the changing needs of the learners. Digital technologies offer us promising opportunities to respond to and incorporate into the practice of educational assessment some of the emerging epistemologies. Epistemologies that may be integral to the effort to deliver high quality education to learners with diverse characteristics and life circumstances in our society. Exploration on development on technology, applied to how we conceptualized and implement assessment may help in the education enterprise to prepare learners for the challenges of the twenty first century workplace. Gordon commissioner and senior scholar Eva Baker (2012) observe that there are at least three rational approaches to dealing with the unpredictability of job and learning requirement in changing global context: 1) educational systems must become both operational and politically agile. 2) Assessment should always include task that call for transfer or the application of learning to new unexpected task, 3) learning and assessment should focus on more pervasive skills that could be embedded in different context and changing subject matter directed toward new applications. Baker identifies two simple and clear policy actions. First transfer must be regularly included as part of test or assessment used to measure learning. Second is to investigate the use of cognitive, interpersonal and intrapersonal skills which is understand as a type of interaction we expect to be demonstrated with components that interact with one another.